2016
DOI: 10.18203/2320-6012.ijrms20163766
|View full text |Cite
|
Sign up to set email alerts
|

Liquid gastric emptying time 1/2 in infants: establishing reference range and it's co-relation with presence of gastro-esophageal reflux

Abstract: INTRODUCTIONGastric emptying time ½ (GET ½) is considered as the half time taken for chyme to pass into the duodenum. Gastric emptying depends upon numerous factors, both endogenous and exogenous. Nerve and hormones along with volume of meal, pH, particle size, composition and viscosity play part in gastric emptying.1 In infant population, gastric emptying also depends upon the maturity at the time of birth. The gastric emptying pattern is different in infants fed with breast milk and formula feeds and so gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…[ 237 ] Prolongation of liquid gastric emptying half-time was observed with increasing severity of GERD (LOE- Low). [ 238 ] The adult normative data for gastric emptying for solids may be inappropriate for children (5–18 years) (LOE- Low). [ 239 ] In a serial GUS study on stable preterm infants, breast milk composition was found to influence gastric emptying, with feeds of higher casein content emptying faster while fortified mother's milk emptying much slower than unfortified mother's milk (LOE- Low).…”
Section: Paediatric Sectionmentioning
confidence: 99%
“…[ 237 ] Prolongation of liquid gastric emptying half-time was observed with increasing severity of GERD (LOE- Low). [ 238 ] The adult normative data for gastric emptying for solids may be inappropriate for children (5–18 years) (LOE- Low). [ 239 ] In a serial GUS study on stable preterm infants, breast milk composition was found to influence gastric emptying, with feeds of higher casein content emptying faster while fortified mother's milk emptying much slower than unfortified mother's milk (LOE- Low).…”
Section: Paediatric Sectionmentioning
confidence: 99%